Controls of Late Jurassic-Early Cretaceous tectonic event on source rocks and seals in marine sequences,South China - Jin, ZhiJun; Yuan, YuSong; Liu, QuanYou; Wo, YuJin (Science China. Earth sciences, 2013)
Thermal evolution of source rocks and dynamic sealing evolution of cap rocks are both subjected to tectonic evolution.The marine sequences in South China have experienced superposed structural deformation from multiple tectonic events.To investigate the effectiveness of preservation conditions,it is of great importance to understand the controls of key tectonic events on the dynamic evolution of cap rocks.This paper discusses the controls of Late Jurassic-Early Cretaceous（J3-K1） tectonic event on source and cap rocks in marine sequences in South China based on the relationships between J3-K1 tectonic event and the burial history types of the marine sequences,the hydrocarbon generation processes of marine source rocks,the sealing evolution of cap rocks,the preservation of hydrocarbon accumulations,and the destruction of paleo-oil pools.The study has the following findings.In the continuously subsiding and deeply buried areas during the J3-K1 period,marine source rocks had been generating hydrocarbons for over a long period of time and hydrocarbon generation ended relatively late.At the same time,the sealing capacity of the overburden cap rocks had been constantly strengthened so that hydrocarbons could be preserved.In the areas which suffered compressional deformation,folding and thrusting,uplifting and denudation in J3-K1,the burial history was characterized by an early uplifting and the hydrocarbon generation by marine source rocks ended（or suspended） during the J3-K1 period.The sealing capacity of the cap rocks was weakened or even vanished.Thus the conditions for preserving the hydrocarbon accumulations were destroyed.The continuously subsiding and deeply buried areas during the J3-K1 period are the strategic precincts of the petroleum exploration in marine sequences in South China.